Strategic Leadership Model in the Hospitality Industry: SWOT Analysis - Verawati, Dian; Yudhanto, Wildan; Giovanni, Axel; Ikhwan, Khairul; Hartono, Budi (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research aims to identify developments in business performance in the hotel industry in the area around the Borobudur Temple Area, identify strategic leadership policies led by women to enhance business performance in the hotel industry, and formulate a successful female leadership strategy model for improving hotel business performance. The research employs a case study approach using a Strengths-Weaknesses-Opportunities-Threats (SWOT) analysis. The study was conducted within the hotel business sector in Magelang Regency. Data collection techniques were based on structured interviews. The research results, as depicted in the SWOT matrix diagram, reveal that the hospitality industry business in the Borobudur area falls within quadrant 1, indicating a highly profitable situation. The hospitality sector in the Borobudur area boasts both strengths and opportunities, allowing it to capitalize on these favorable conditions. The recommended strategy for this situation is the implementation of growth-oriented policies. Keywords: Business Performance, Strategic Leadership Model, Women’s Leadership, SWOT Analysis, Hospitality Industry ABSTRAK Penelitian ini bertujuan untuk mengidentifikasi perkembangan kinerja bisnis pada industri perhotelan di wilayah sekitar Kawasan Candi Borobudur, mengidentifikasi kebijakan kepemimpinan strategis perempuan untuk mendorong kinerja bisnis industri perhotelan, dan merumuskan model strategi kepemimpinan perempuan yang sukses untuk peningkatan kinerja bisnis perhotelan. Penelitian ini mengadopsi pendekatan studi kasus dengan basis Strengths-Weaknesses-Opportunities-Threats (SWOT). Penelitian dilaksanakan pada bisnis perhotelan di Kabupaten Magelang. Teknik pengumpulan data dilakukan dengan wawancara terstruktur. Hasil penelitian dalam diagram matrik SWOT menunjukan usaha industri hospitalitasdi Kawasan Borobudur berada pada kuadran 1 yaitu merupakan situasi yang sangat menguntungkan. Hospitalitas di Kawasan Borobudur tersebut memiliki peluang dan kekuatan sehingga dapat memanfaatkan peluang yang ada. Strategi yang harus diterapkan dalam kondisi ini adalah mendukung kebijakan pertumbuhan yang agresif. Kata kunci: Kinerja Bisnis, Model Kepemimpinan Strategik, Kepemimpinan Perempuan, SWOT Analysis, Industri Perhotelan